2013
DOI: 10.1007/s10495-013-0911-x
|View full text |Cite
|
Sign up to set email alerts
|

The apoptosis of peripheral blood lymphocytes promoted by hyperbaric oxygen treatment contributes to attenuate the severity of early stage acute pancreatitis in rats

Abstract: The aim of this study was to investigate the immunoregulatory effects of hyperbaric oxygen (HBO) via promoting the apoptosis of peripheral blood lymphocytes (PBLs) to attenuate the severity of early stage acute pancreatitis (AP) in rats. Additionally, the persistence of the HBO treatment effects was evaluated. One hundred and twenty male Wistar rats were randomized into four groups: sham, AP, AP + normobaric oxygen (NBO), and AP + HBO. Each group consisted of 30 rats. Four hours after the induction of AP, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 91 publications
2
24
1
Order By: Relevance
“…There was a positive correlation between the incubated level of H 2 S and histological score. The level of HMGB1, a well‐known member of damage‐associated molecular patterns released from the nuclei of necrotic cells , was detected by immunoblot (Fig. C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a positive correlation between the incubated level of H 2 S and histological score. The level of HMGB1, a well‐known member of damage‐associated molecular patterns released from the nuclei of necrotic cells , was detected by immunoblot (Fig. C).…”
Section: Resultsmentioning
confidence: 99%
“…A model of AP in rats was established using the method as previously described . Briefly, the rats were anaesthetized by an intra‐peritoneal injection of sodium pentobarbital (40 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Hyperbaric oxygen (HBO) therapy also has been investigated in previous experimental studies that have significantly improved TOSp 12 and apoptosis in SAP. 13 , 14 Thereafter, more recent studies by HBO in AP indicated that enhanced inflammatory response, 15 cytokines levels, 16 TOSp, and THSc. 17 , 18 …”
mentioning
confidence: 99%
“…Their results showed the peak levels of polymorphonuclear leukocyte elastase (PMNE) and thrombomodulin (TM) were diminished and delayed, and the elevated expression of CD18 (a protein related to leukocyte adhesion) was clearly suppressed after HBO exposure. In the rats with acute pancreatitis, Bai et al (2014) found HBO could induce the apoptosis of peripheral blood lymphocytes to attenuate the disease.…”
Section: Effects Of Hbo On Organ Preservationmentioning
confidence: 98%